Estabilidade para equações discretas autônomas - Zibiani, Edilson [UNESP] (2015)
This work presents a study about stability of the null equilibrium of autonomous discrete equations by Liapunov's Method and Method of Dichotomic Maps, which is an extension of the Liapunov's Method